Pengembangan Taman Toga Sebagai Bahan Baku Resep Toga Berbasis Biosaince pada Kelompok Pkk Rw 7 Bangkong Kecamatan Gunungpati Kota Semarang - Iswari, Retno Sri; R. Susanti, R. Susanti; Saptono, Sigit; Sasi, Fitri Arum; Laila, Nafisatul (Universitas Negeri Semarang, 2021)
The spread of the COVID-19 virus that has occurred recently is fast the antiviral drugs are not yet available. The spread has to reduce the virus for mild sufferers, self-isolation is requested and for severe sufferers to be isolated in the hospital. One of the efforts to prevent the transmission of COVID-19 is to increase endurance through the use of family medicinal plants (Toga). The potential of medicinal plants as immunomodulators is widely spread in Bangkong village. Bangkong is one of the sub-districts in Semarang City that is also affected by Covid-19, each resident has enough yard to make Toga park. This service activity aims to: (1) provide skills to PKK RW 7 women in designing Toga gardens by making Toga plant racks to decorate their home gardens which can serve as the basic ingredients for making ethnoscience-based Toga recipes; (2) providing knowledge and skills in cultivating Toga; (3) providing knowledge and skills in making ethnoscience-based herbal recipes; (4) providing skills in compiling ethnoscience-based cookbooks about the benefits and ways of presenting them. The approach methods used in the implementation are workshops, lectures/outreach, and training / mentoring. The workshop, given to convey theoretical knowledge about landscape architecture based on land area. In this activity the community service team explained how to make Toga's garden suitable for the land, looking beautiful and free from being damaged by chickens. The results of the training were agreed by the PKK mothers to make Toga in the form of a shelf. It is hoped that the training at the first meeting will produce Toga garden designs that can ensure that each Toga plant can live freely without being disturbed by one another. The lecture method is carried out to explain the benefits of medicinal plants, types of medicinal plants, how to reproduce, and how to treat them. The training method is carried out to provide skills to mothers in making recipes and herbal medicine that can be used to prevent Covid-19 infection. Mothers are very responsive in participating in extension activities on various kinds of plants that can increase endur. After participating in this activity, mothers have understood well the benefits of Toga to increase endurance and prevent being infected with the Corona - 19 viruses Keywords: Bangkong Semarang, Eetnoscience, Taman toga, Bangkong Semarang, Eetnoscience, Taman toga Penyebaran virus covid-19 yang terjadi akhir-akhir ini sangat cepat, obat antivirus belum tersedia. Untuk mengurangi penyebaran virus bagi penderita ringan diminta isolasi diri dan bagi penderita berat diisolasi di rumah sakit. Salah satu upaya pencegahan penularan covid-19 adalah dengan meningkatkan daya tahan tubuh melalui pemanfaatan tanaman obat keluarga (Toga). Potensi tanaman obat sebagai imunomodulator sangat banyak tersebar di lingkungan desa Bangkong. Bangkong merupakan salah satu kelurahan di Kota Semarang juga terdampak covid-19, tiap warga mampunyai halaman yang cukup untk membuat taman Toga. Kegiatan pengabdian ini bertujuan untuk: (1) memberikan keterampilan kepada ibu-ibu PKK RW 7 mendesain taman Toga dengan membuat rak tanaman Toga sebagai penghias halaman rumah yang dapat berfungsi sebagai bahan dasar membuat resep Toga berbasis etnoscience; (2) memberikan pengetahuan dan keterampilan dalam membudidayakan Toga; (3) memberikan pengetahuan dan keterampilan dalam membuat membuat resep jamu berbasis etnoscience; (4) memberikan keterampilan menyusun buku resep berbasis etnoscience tentang manfaat dan cara penyajiannya. Metode pendekatan yang digunakan dalam pelaksanaan adalah workshop, ceramah/penyuluhan, dan pelatihan/pembimbingan. Workshop, diberikan untuk menyampaikan pengetahuan teoritis tentang arsitektur lanskap berdasarkan luas lahan. Pada kegiatan ini team pengabdian menjelaskan bagaimana membuat taman Toga yang sesuai dengan lahan, terlihat indah dan terbebas dirusak oleh ayam. Hasil pelatihan disepakati para ibu PKK membuat Toga dalam bentuk Rak. Pelatihan di pertemuan pertama diharapkan dihasilkan disain taman Toga yang dapat menjamin masing-masing tanaman Toga bisa hidup bebas tidak saling terganggu. Metode ceramah dilakukan untuk memberikan penjelasan tentang manfaat tanaman obat, jenis-jenis tanaman obat, cara memperbanyak dan cara perawatannya. Metode pelatihan dilakukan untuk memberikan keterampilan kepada ibu-ibu dalam membuat resep dan jamu yang dapat digunakan mencegah terkena Covid - 19Setelah mengikuti kegiatan ini, ibu-ibu sudah memahami dengan baik manfaat Toga untuk meningkatkan daya tahan tubuh dan mencegah terinfeksi virus Corona – 19 Keywords: Bangkong Semarang, Eetnoscience, Taman toga, Bangkong Semarang, Eetnoscience, Taman toga